Violette Nozière : a story of murder in 1930s Paris - Maza, Sarah C., 1953- (University of California Press, 2011)
On an August evening in 1933, in a quiet, working-class neighborhood in Paris, eighteen-year-old Violette Nozière gave her mother and father glasses of barbiturate-laced "medication," which she told them had been prescribed by the family doctor; one of her parents died, the other barely survived. Almost immediately Violette's act of "double parricide" became the most sensational private crime of the French interwar era, discussed and debated so passionately that it was compared to the Dreyfus Affair